2016
DOI: 10.1002/hipo.22609
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform allocation of hippocampal neurons to place fields across all hippocampal subfields

Abstract: The mechanisms governing how the hippocampus selects neurons to exhibit place fields are not well understood. A default assumption in some previous studies was the uniform random draw with replacement (URDWR) model, which, theoretically, maximizes spatial "pattern separation", and predicts a Poisson distribution of the numbers of place fields expressed by a given cell per unit area. The actual distribution of mean firing rates exhibited by a population of hippocampal neurons, however, is approximately exponent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 66 publications
11
27
1
Order By: Relevance
“…Recent data have shown that a subset of cells in a hippocampal neural ensemble activated during an episode of exploration may be used redundantly when the environment changes, such that a greater number of cells have place fields in both environments than would be expected by chance (Alme et al, 2010; Mizuseki and Buzsáki, 2013; Buzsáki and Mizuseki, 2014; Witharana et al, 2016). This is believed to reflect skewed, high firing rate cells that are more likely to remain active across multiple environments (Mizuseki and Buzsáki, 2013; Buzsáki and Mizuseki, 2014; Witharana et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent data have shown that a subset of cells in a hippocampal neural ensemble activated during an episode of exploration may be used redundantly when the environment changes, such that a greater number of cells have place fields in both environments than would be expected by chance (Alme et al, 2010; Mizuseki and Buzsáki, 2013; Buzsáki and Mizuseki, 2014; Witharana et al, 2016). This is believed to reflect skewed, high firing rate cells that are more likely to remain active across multiple environments (Mizuseki and Buzsáki, 2013; Buzsáki and Mizuseki, 2014; Witharana et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…This is believed to reflect skewed, high firing rate cells that are more likely to remain active across multiple environments (Mizuseki and Buzsáki, 2013; Buzsáki and Mizuseki, 2014; Witharana et al, 2016). One way to examine the extent that neural ensembles follow a skewed excitability distribution rather than adhere to a uniform random draw with replacement (URDWR) model is to compare the expected percent of active cells across multiple epochs of exploration (Px) relative to the observed percent of cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mechanisms that govern the selection of the actual subset of active PCs in a given environment remain unknown. The simplest scenario would be a random allocation of place cells 116 to maximize the separation of neuronal representations in different environments (‘pattern separation’ or remapping 117119 ). However, recent experiments challenge this model, demonstrating that firing rate distributions of CA1PCs are skewed (log-normally distributed) 120 , the firing activity of each cell is largely preserved across behavioral states 120 , and hippocampal PCs may even be, at least in part, preselected for activation 121,122 .…”
Section: Open Questions About Heterogeneity Of Principal Neurons In Tmentioning
confidence: 99%